ANALISIS KESALAHAN SISWA SD DALAM MENYELESAIKAN SOAL PERKALIAN BERSUSUN BERDASARKAN TEORI KASTOLAN - Zuhriana, Winda Agil; Pangestuti, Diana; AL Fath, Ayatullah Muhammadin; Hutagalung, Erwin Efendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the fact that many elementary school students still experience difficulties in understanding basic mathematical concepts, especially in long multiplication operations. These difficulties often lead students to make various errors in understanding place value concepts and calculation procedures, which impact low learning outcomes and student numeracy skills. This study aims to analyze the types of errors made by elementary school students in solving long multiplication problems based on Kastolan's theory through a Systematic Literature Review (SLR) approach. The method used is a Systematic Literature Review (SLR) by reviewing 10 relevant scientific articles published between 2021 and 2025 from the Google Scholar database. Data analysis was conducted by classifying errors into three categories according to Kastolan's theory: conceptual errors, procedural errors, and technical errors. The results show that the most dominant error made by students is conceptual error with an average of 52.7%, followed by procedural error at 45.45%, and technical error at 42.13%. These findings indicate that low understanding of basic multiplication and place value concepts is the main factor causing student errors, which then leads to procedural and technical calculation errors. The results of this study are expected to serve as a reference for teachers in designing more effective learning strategies to improve students' understanding of mathematical concepts.